Mass spectrometric assays reveal discrepancies in inhibition profiles for the SARS-CoV-2 papain-like protease - Brewitz, L; Kamps, JJAG; Lukacik, P; Strain-Dammerell, C; Zhao, Y; Tumber, A; Malla, T; Orville, A; Walsh, M; Schofield, C (Wiley, 2022)
The two SARS-CoV-2 proteases, i.e. the main protease (Mpro) and the papain-like protease (PLpro), which hydrolyze the viral polypeptide chain giving functional non-structural proteins, are essential for viral replication and are medicinal chemistry targets. We report a high-throughput mass spectrometry (MS)-based assay which directly monitors PLpro catalysis in vitro. The assay was applied to investigate the effect of reported small-molecule PLpro inhibitors and selected Mpro inhibitors on PLpro catalysis. The results reveal that some, but not all, PLpro inhibitor potencies differ substantially from those obtained using fluorescence-based assays. Some substrate-competing Mpro inhibitors, notably PF07321332 (nirmatrelvir) which is in clinical development, do not inhibit PLpro . Less selective Mpro inhibitors, e.g. auranofin, inhibit PLpro , highlighting the potential for dual PLpro/Mpro inhibition. MSbased PLpro assays, which are orthogonal to widely employed fluorescence-based assays, are of utility in validating inhibitor potencies, especially for inhibitors operating by non-covalent mechanisms